Low-Temperature Biosynthesis of Fluorescent Semiconductor Nanoparticles (Cds) by Oxidative Stress Resistant Antarctic Bacteria - Vasquez-Guzman, C; Monras-Charles, J (Elsevier, 2014)
Bacterial biosynthesis of nanoparticles represents a green alternative for the production of nanostructures with novel properties. Recently, the importance of antioxidant molecules on the biosynthesis of semiconductor fluorescent nanoparticles (quantum dots, QDs) by mesophilic bacteria was reported. The objective of this work was the isolation of psychrotolerant, oxidative stress-resistant bacteria from Antarctica to determine their ability for biosynthesizing CdS QDs at low temperatures. QDs biosynthesis at 15°C was evaluated by determining their spectroscopic properties after exposing oxidative-stress resistant isolates identified as Pseudomonas spp. to Cd2+ salts. To characterize the QDs biosynthetic process, the effect of metal exposure on bacterial fluorescence was determined at different times. Time-dependent changes in fluorescence color (green to red), characteristic of QDs, were observed. Electron microscopy analysis of fluorescent cells revealed that biosynthesized nanometric structures localize at the cell periphery. QDs were purified from the bacterial isolates and their fluorescence properties were characterized. Emission spectra displayed classical CdS peaks when excited with UV light. Thiol content, peroxidase activity, lipopolysaccharide synthesis, metabolic profiles and sulfide generation were determined in QDs-producing isolates. No relationship between QDs production and cellular thiol content or peroxidase activity was found. However, sulfide production enhanced CdS QDs biosynthesis. In this work, the use of Antarctic psychrotolerant Pseudomonas spp. for QDs biosynthesis at low temperature is reported for the first time. © 2014 Elsevier B.V.